IMPROVING THE STUDENTS™ ABILITY IN WRITING RECOUNT TEXT BY APPLYING JIGSAW TECHNIQUE - Ardila, Ridha; Ginting, Siti Aisah (TRANSFORM: Journal of English Language Teaching and Learning, 2013)
ABSTRACT This study concerns on improving the students™ ability in writing recount text by applying jigsaw technique. The underlying objective of this study is to investigate whether teaching recount by applying Jigsaw Technique potentially improves students™ skill. The research was conducted by using Classroom Action Research (CAR). The population was the 2011-2012 eight grade students of SMP Negeri 1 H.Perak. The number of students was 36, consisting of females and males. The procedure of the research was administrated into two cycles where each cycle consisted of four meetings. Each meeting included four steps namely: planning, action, observation, and reflection. There were two kinds of data collected during the study, qualitative and quantitative data. The instrument for collecting the quantitative data was the writing of recount test while the qualitative data were gathered by using interview, diary notes and observation sheet. Based on the data analysis, the mean of students™ score in Test I was 28.75; for the Test II was 63.88, and for the Test III was 75.83. The qualitative data showed that the students were interested in the applying of Jigsaw Technique. The conclusion is that the application of Jigsaw Technique in writing recount text improves the students™ ability in writing recounts. Key words: jigsaw technique, writing recounts, eight grade students